Parents’ Perspectives on Inclusive Schools for Children with Autism Spectrum Conditions - Falkmer, M.; Anderson, K.; Joosten, Annette; Falkmer, Torbjorn (Routledge, 2015)
Children with autism spectrum conditions (ASC) increasingly participate in inclusive education. The present study reviewed studies of children with ASC for parents’ perceptions of aspects they believed contributed to inclusive mainstream school settings. Understanding the parental perspective on the facilitators for inclusion of their child with ASC in mainstream schools is likely to improve inclusive practice. Twenty-eight empirical articles revealed that parents perceived teachers as playing a vital role in the inclusion of their children with ASC. The school was considered important in creating an environment that enabled inclusion, particularly through positive peer relations, prevention of bullying and help from support staff. At the societal level, funding and legislative policies were considered important. By understanding these aspects, policy-makers, teachers, school administrators and therapists may better be able to address parents’ inclusion concerns and thereby develop strategies to improve inclusion in mainstream schools.